Pengaruh Vitamin D dalam Menurunkan Kadar Protein C-Reaktif pada Kolitis Ulserativa: Laporan Kasus Berbasis Bukti: Laporan Kasus Berbasis Bukti - Batubara, Irawati Friana; Sonia, Steffi (Cermin Dunia Kedokteran, 2026)
Introduction: Ulcerative colitis (UC) is a chronic gastrointestinal inflammatory disease characterized by immune dysregulation. C-reactive protein (CRP) is used as a marker of inflammation and disease severity. Vitamin D has an immunomodulatory role, and low serum levels are associated with increased disease activity in UC. However, the effect of vitamin D supplementation on inflammatory markers in UC remains unclear. This study aims to evaluate the effect of vitamin D supplementation on CRP levels in patients with UC. Methods: A systematic literature search was conducted across three databases: PubMed, Scopus, and the Cochrane Library. The search strategy was developed based on the PICO approach, with filters for randomized controlled trials and meta-analyses. Duplicates were removed, and selection was carried out based on titles, abstracts, and full texts. The selected studies were critically appraised using the validity, significance, and applicability approach from the Centre for Evidence-Based Medicine. Results: Two studies met the criteria, one systematic review and meta-analysis, and one meta-analysis. Although both studies showed a significant reduction in CRP levels after vitamin D administration, the validity of these studies remains doubtful. Conclusion: Current evidence is insufficient to support a definitive recommendation for the use of vitamin D supplementation in patients with ulcerative colitis. High-quality randomized controlled trials are needed.